VOLATILITAS INFLASI DAERAH DI INDONESIA: FENOMENA MONETER ATAU FISKAL? - Trisdian, Paula Adiati; Pratomo, Yulius; Saraswati, Birgitta Dian (Universitas Kristen Satya Wacana, 2016)
This research aims to analyse the regional inflation volatility in Indonesia for the period of 1999-2009 from both monetary and fiscal sides. The data employed in this study are regional panel data consisting of 275 observations picked from several publications. The method of analysis used in this study is Fixed Effect Model. The proxy of monetary side is outstanding of loans in Rupiah and Foreign Currency of commercial and rural banks by project location of Provinces, and fiscal side is local government debt. This research finds both monetary and fiscal sides have positive relationship with the inflation volatility in Indonesia. However, only monetary side which has significant impact, but fiscal side does not. This finding further shows that the regional inflation in Indonesia is still a monetary phenomenon. Therefore, the solution to controll regional inflation in Indonesia is to manage credit rationing conducting by commercial and rural banks for every province.